Leadership and strategic planning practice: basis for quality education - Lasisi, Abbas Ayodele; Mohd Ali, Hairuddin; S. N., Yassin (Binary University College, Malaysia, 2011)
This present study was embedded in strategic planning theories and motivational concepts and theories; the ancient Chinese strategic theories in relation with other researchers' theories and models that explain the process of strategic planning in educational sector. it defined leadership as the lifting of people's vision to a higher sight, the raising of their performance to a higher standard, the building of their personality beyond its normal limitations. The aim of this research is to investigate the extent to which leaders able to motivate and supervise the educators by implementing the strategic planning process as basis for quality education. The findings from this research was consistence with Selznick (1957) who concluded that effective leaders should be able to define and defend the institutional values and its distinctive mission of an organization to achieve quality. This research is a quantitative in nature that employed factor analysis in explaining its findings. The findings from this study would be of benefit to school managers, stakeholders and as well as customers for quality achievement.